Polymeric Micelles of Biodegradable Diblock Copolymers: Enhanced Encapsulation of Hydrophobic Drugs - Yasser H. A. Hussein (Materials, 2018)
Polymeric micelles are potentially efficient in encapsulating and performing the controlled release of various hydrophobic drug molecules. Understanding the fundamental physicochemical properties behind drug–polymer systems in terms of interaction strength and compatibility, drug partition coefficient (preferential solubilization), micelle size, morphology, etc., encourages the formulation of polymeric nanocarriers with enhanced drug encapsulating capacity, prolonged circulation time, and stability in the human body. In this review, we systematically address some open issues which are considered to be obstacles inhibiting the commercial availability of polymer-based therapeutics, such as the enhancement of encapsulation capacity by finding better drug–polymer compatibility, the drug-release kinetics and mechanisms under chemical and mechanical conditions simulating to physiological conditions, and the role of preparation methods and solvents on the overall performance of micelles.